Generalized and flexible modulation options - Jaradat, Ahmed M.; Hamamreh, Jehad M.; Arslan, Hüseyin (Institution of Engineering and Technology, 2020)
Flexibility support is critical for fifth generation (5G) and beyond radio access technologies (RATs) to meet diverse applications, channel conditions, and user requirements. Besides the flexible waveform design discussed in Chapter 4, modulation design emerges as another degree of freedom that can be powerful for the design of 5G and beyond RATs. The basic relation of waveform with modulation is discussed in this chapter. A unified and inclusive framework is presented for various modulation options by exploring different dimensions, including index, number, shape, etc. Furthermore, some future modulation candidates are envisioned for 5G and beyond RATs.
Keywords: Modulation Options; Electrical and Electronics; Engineering